Neighborhood Disorder, Social Support, and Outcomes Among Violence-Exposed African American Women - Pickover, Alison M. (J Interpers Violence, 2018)
Intimate partner violence (IPV) against women, particularly those living in poverty who have multiple marginalized identities, is a significant public health issue. IPV is associated with numerous mental health concerns including depression, hopelessness, and suicidal behavior. The present study examined the ecological determinants of these mental health outcomes in a high-risk sample of 67 low-income, African American women survivors of IPV. Based on an ecological framework that conceptualizes individuals as nested in multiple, interactive systems, we examined, longitudinally, the main and interactive effects of self-reported neighborhood disorder and social support from family members and friends on participants’ mental health (i.e., self-reported depressive symptoms, hopelessness, and suicide intent). In multiple regression analyses, neighborhood disorder interacted with social support from family members to predict depressive symptoms and hopelessness over time. Neighborhood disorder also interacted with social support from friends to predict hopelessness and suicide intent over time. High levels of social support buffered against the dangerous effects of neighborhood disorder on depressive symptoms, hopelessness, and suicide intent; at low levels of social support, there was no significant association between neighborhood disorder and those mental health outcomes. Neighborhood disorder and social support did not yield significant main effects. These findings underscore the importance of interventions that target individuals, families, and communities (e.g., community empowerment programs). Group interventions may also be important for low-income, African American women survivors of IPV, as they can help survivors establish and strengthen relationships and social support.